Griglie di lettura e analisi dell’islam europeo. Diritto interculturale e relazioni sciaraitiche (Stato, Chiese e pluralismo confessionale, 2016)
Lo scritto, sottoposto a valutazione, rappresenta la versione ampliata e rivista di un intervento dal titolo ‘Riflessioni contemporanee su Europa ed islām’ svolto il 1° dicembre 2015 all’Università degli Studi di Torino, quale parte del ciclo di incontri “Le relazioni familiari nel diritto interculturale. Diritto interculturale tra ordinamenti statali e religioni. Tecniche di adattamento dei diritti religiosi”; è destinato alla pubblicazione negli atti del ciclo di incontri “Le relazioni familiari nel diritto interculturale. Diritto interculturale tra ordinamenti statali e religioni”, nel volume Relazioni familiari nel diritto interculturale, a cura di I. Zuanazzi, Libellula University Press, Tricase, 2017. Alla data dell’intervento l’A. era Ricercatore Incoming presso il Dipartimento di Giurisprudenza dell’Università degli Studi di Torino e anche Teaching Fellow presso la School of Law, School of Oriental and African Studies (SOAS), University of London.SOMMARIO: 1. Introduzione - 2. Tassonomie di appartenenza alla Ummah - 3. Modelli di innesto dell’islām in Europa - 4. Atteggiamenti culturalizzati, assimilati, cosmopoliti e in protesta - 5. Approcci geopoliticizzati e transnazionali - 6. Orientamenti esternalizzati, dualizzati e islamizzati - 7. Considerazioni conclusive.  Decoding European islām. Intercultural law and sharīʿah-compliant relations.ABSTRACT: Since the beginning of the XXI century, Islām became a key-topic in the national and international discourse. In the contemporary pluralist and fluid scenario, the public visibility of Euro-Islām increases also as expression of Muslim communities’ demands and pressing needs. In light of recent tragic events and the exponentially growing European Muslim community, developing appropriate tools for effective and fruitful dialogue is thus of pivotal importance.Adopting a pluralist perspective, the paper investigates the multi-folded accommodation, adaptation and mutual adjustment techniques enacted amongst different legal cultures, orders and systems. Specifically, attention is paid to the reciprocally (non) adjustments of Islamic/Muslim laws to European domestic legal systems, and the implications of the interaction between sharīʿah-compliant relations and intercultural law.The proposed analysis aims to decode the various forms of sharīʿah-compliant modus vivendi enacted by European Muslims by shedding light upon the peculiarities of European Islām and the polychrome taxonomies of belonging to al-Ummah Islamiyyah. Relying upon field-collected data, the transplantation models of Islām in national legal systems are disentangled, whilst the discussion reveals new prototypes of state and social co-existence, constantly developed and reinvented at the crossroads amongst states, religions and traditions.